Welsh Spain effort (circular)
032-0097-001 SOUTH WALES REGIONAL COUNCIL OF LABOUR. Dear Comrade, Transport House, 42, Charles Street, CARDIFF, 17/2/39. WELSH SPAIN EFFORT. I have pleasure in giving below full details of the money raised by the various organisations in South Wales in response to our appeal for aid for Spain. Yours sincerely, George Morris, Secretary.- Name of Organisation. Amount. £.s.d. Llansamlet War Labour Party 0.10.6 Briton Ferry Trades Council & Labour Party 20.0.0 N.U.D.A.W. South Wales Branches 7.0.0 Coun. W. F. Jackson, Hereford 1.1.0 Swansea Labour Association 40.0.0 Llanelly D.L.P. 50.0.0 Rhondda West D.L.P. 39.0.0 Assoc. Society of Moulders, Neath Branch 1.15.0 Aberdare Trades Council & Labour Party 9.0.0 Neath D.L.P. 40.6.7 Glyncorrwg Ward Labour Party 7.5.0 Glyncorrwg Local Labour Party 1.1.0 Nantyglo & Blaina Trades Council 7.10.3 Swansea Labour Association 20.0.0 Coal Trimmers' Union 1.1.0 Cwmavon Ward Labour Party 2.3.10 Bryn Lodge, S.W.M.F. 3.0.0 Abercynon Lodge, S.W.M.F. 1.1.0 Gwenallt Lodge, S.W.M.F. 0.10.0 Taibach Ward Labour Party 10.0.0 Elliot Lodge, S.W.M.F. 1.1.0 Beynon Lodge, S.W.M.F. 1.1.0 Cory Hall Collection - 21/1/39 4.10.0 Gelliceidrim Lodge, S.W.M.F. 1.0.0 Pwllgwaun Lodge, S.W.M.F. 0.10.0 Rhondda West D.L.P. 11.0.0 Roath Ward Labour Party, Cardiff 1.7.6 Ogmore Valley Joint Committee 7.10.0 Ystalyfera Labour Party 20.0.0 Caerphilly Workmen's Institute 2.2.0 Bargoed Surface Lodge, S.W.M.F. 1.0.0 Maesteg Lodge, S.W.M.F. 28.7.7 Markham Lodge, S.W.M.F. 5.0.0 Bedwas and Machen Trades Council 12.8.8 Oakdale Lodge, S.W.M.F. 5.0.0 Blaengwynfi Public Meeting per Mr. Windsor Williams 9.2.6 -do -do- 1.7.6 Pontypool Trades Council 13.14.6 TOTAL £308.7.5 GOODS to the value of at least £600. have been despatched in two consignments by boat to Government Spain. This food has been collected by various centres throughout South Wales. This result is a remarkable tribute to the sacrifice made by our people on behalf of the long-suffering people in Government Spain. Collections of food and money are still proceeding. 292/946/32/97